Improving energy efficiency of apple production by reduced application of pesticides - Sedlar, Aleksandar; Ponjičan, Ondrej; Kiss, Ferenc; Bugarin, Rajko; Višacki, Vladimir; Radojčin, Milivoj; Kešelj, Krstan (International Journal of Agricultural and Biological Engineering, 2020)
A large number of apple orchards are treated over 20 times during the vegetation period with high application rates (over 1000 L/hm2) or medium application rates (500-1000 L/hm2) of pesticides which require significant energy input. Experimental research was carried out in the Serbian region of Vojvodina with the aim to show the possibilities to reduce energy usage in apple production by reducing pesticide application rates (200-500 L/hm2) and smaller controlled number of treatments with pesticides while maintaining the biological efficiency of apple chemical protection. Research results showed that the cumulative life cycle energy demand of apple production in Vojvodina, assuming a typical 22 annual treatments and relatively high pesticide application rate (1150 L/hm2), was 48 GJ/hm2 and energy output was 94 GJ/hm2. Reduced number of treatments and lower pesticide application rates have a favorable impact on energy inputs associated with diesel fuel, machinery, chemicals, water and electricity consumption and usage, whereas other energy inputs remain unchanged. The energy input for 12 treatments with pesticide application rates of 381 L/hm2 was 36 GJ/hm2, which is a 25% reduction in comparison to 22 treatments with a pesticide application rate of 1150 L/hm2. Reduced number of treatments and pesticide application rate increased the energy use efficiency from 1.96 to 2.61, energy productivity from 0.82 kg/MJ to 1.09 kg/MJ, and net energy from 46 GJ/hm2 to 58 GJ/hm2. Results also suggest that applying the correct IPM approach can easily lead to a strong reduction in the number of treatments and a major energy saving. Keywords: apple production, energy flow, pesticide application rates, total energy input, energy balancing DOI: 10.25165/j.ijabe.20201304.5743 Citation: Sedlar A, Ponjičan O, Kiss F, Bugarin R, Višacki V, Radojčin M, et al. Improving energy efficiency of apple production by reduced application of pesticides. Int J Agric & Biol Eng, 2020; 13(4): 93–102.